L-Shaped Arthroscopic Posterior Capsular Release in Frozen Shoulder - Mohamed Gamal Morsy MD; Ahmed Hassan Waly MD; Mostafa Ashraf Galal MD; El Hussein Mohamed Ayman MD; Hisham Mohamed Gawish MD (SAGE Publishing, 2021)
Background: The inadequate arthroscopic release of the tight posterior capsule in frozen shoulder may result in limited postoperative shoulder internal rotation. Indication: The purpose of this article is to describe an L-shaped arthroscopic posterior capsular release to overcome the limited internal rotation that may be encountered following the standard longitudinal technique. Operative intervention is indicated in patients with refractory shoulder stiffness with limitation of internal rotation of grade 0, +2, +4 (according to the Constant-Murley Score), after failure of conservative measures for 3 to 6 months. The technique is contraindicated if less than 3 months of physical therapy, shoulder stiffness due to osseous deformity, infection, or cuff tear arthropathy. Technique: After performing a standard anterior capsular release, the scope is shifted to the anterior portal to perform posterior capsular release by introducing the radiofrequency ablation device through the posterior portal. Posterior release begins from the glenoid level down to the 6 o'clock position until the back fibers of the infraspinatus muscle appear. Then the hook-tip part of the radiofrequency ablation device is used to perform a transverse release in the posterior capsule, starting from the beginning of the longitudinal limb. The transverse limb is performed in a stepwise manner going step-by-step laterally but ending before reaching the rotator cuff to avoid any damage of the cuff. After that, the shoulder was manipulated according to Codman technique. Results: A comparative study was performed on 43 patients with primary frozen shoulder to compare the standard longitudinal (22 patients) and L-shaped (21 patients) posterior capsular release. At the final follow-up, there was a statistically significant improvement in the internal rotation range of motion in the L-shaped group ( P < .001). There was no loss of function over time. Moreover, there were no infections, instability, or axillary nerve injury in either group. Discussion/Conclusion: Restriction of internal rotation in frozen shoulder has been attributed to posterior capsular tightness. The L-shaped arthroscopic posterior capsular release in patients with primary frozen shoulder significantly improves the postoperative internal rotation range of motion.